Unormowanie przesłanek udzielenia koncesji na prowadzenie kasyna gry a ochrona interesu publicznego - Kopystyński, Konrad (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
Exclusion of application general negative premises of granting a concession from the entrepreneurs law in cases of granting a concession for operating casino games does not cause a limitation of protection of the public interest compared to standard which is appointed by general regulation. Premises of granting the concession for operating casino games from the law on gambling do not have a narrower scope than general negative premises of granting a concession from the entrepreneurs law. That conclusion is based on the comparison between the both regulations. Moreover, on the grounds on the previous freedom of economic activity act, a few general negative premises of granting a concession had a wider scope than premises of granting the concession for operating casino games. Simultaneously, exclusion of application general rules in cases of granting the concession for operating casino games also then was in force. Elimination a few general negative premises in the entrepreneurs law, which were applying on base of the repealed freedom of economic activity act, caused that level of the protection of public interest appointed by scope of general negative premises of granting a concession is not lower than level of the protection of public interest in cases of granting a concession for operating casino games. That solution eliminated a certain systemic inconsistency, which had existed before the entrepreneurs law came into force.
Keywords: gambling; public interest; concession; casino; exclude